Head and Neck Manifestations of Granulomatosis with Polyangiitis (GPA) Mimicking as Carcinoma - Wan Hassan, Wan Ahmad Amiruddin; Othman, Iylia Ajmal; Fuaat, Azliana Abd; Leman, Wan Ishlah; Sidek, Dinsuhaimi (International Journal of Human and Health Sciences (IJHHS), 2022)
Granulomatosis with polyangiitis (GPA) is a rare small vessel vasculitis mainly affecting the upper airway, ocular, renal and pulmonary systems. Its histopathological hallmark is presence of granulomatous inflammation and presence of circulating anti-neutrophil cytoplasm antibodies (c-ANCA) serologically. Most patients with GPA presented with ENT manifestations as their initial or only presentation. As it can mimic other infectious, allergic, and inflammatory diseases, delay in diagnosis is inevitable. A rapid clinical course of the disease may also mimic malignant disease, leading to misdiagnosis. We are reporting a case of a 52-year-old Malay male, who presented to our center with one month history of progressively worsening nasal blockage associated with blood-stained nasal discharge. His initial diagnosis of nasal septum squamous cell carcinoma was disputed from repeated biopsy. Given the multi-organs involvement of the disease, pathognomonic histopathological findings and C-ANCA positivity, the diagnosis of Granulomatosis with polyangiitis (GPA) was made. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 342-347